MENUMBUHKAN SIKAP PERSATUAN MELALUI TRADISI LOPIS RAKSASA DI KOTA PEKALONGAN - Yusuf Rozin; Atiqa Sabardila (Jurnal Budaya Nusantara, 2022)
This article has the following objectives: (1) the background of the giant lopis tradition, (2) when to implement the giant lopis tradition in the krapyak of Pekaongan City, (3) The attitude of unity through the giant lopis tradition in Pekalongan City. This study used a qualitative descriptive method, data collection was carried out by observation and regional archives through the official website of Pekalongan City. The results of this study indicate that the Lopis Giant "syawalan" tradition in Pekalongan City is still carried out from generation to generation and is carried out on the 8th of Shawwal. Krapyak residents carry out sunnah fasting which is highly recommended by KH. Abdullah Sirodj on the 2-7th of Shawwal which then on the 8th of Shawwal the Shawwalan tradition was carried out. This syawalan tradition also increases the sense of unity and mutual cooperation among the people of Krapyak itself and is a reflection that mutual cooperation and unity can strengthen and strengthen ties of kinship.